3D finite element model for reconstructed mixed-conducting cathodes: I. performance quantification - Carraro, Thomas; Joos, Jochen; Rüger, Bernd (Electrochimica acta, 2012)
The performance of a solid oxide fuel cell (SOFC) is strongly affected by electrode polarization losses, which are related to the composition and the microstructure of the porous materials. A model that can decouple the effects associated to the geometrical arrangement, shape and size of the particles together with material distribution on one side and the material properties on the other can give a relevant improvement in the understanding of the underlying processes. A porous mixed ionic-electronic conducting (MIEC) cathode was reconstructed by a tomography technique based on focused ion beam coupled with scanning electronic microscope (FIB/SEM). The detailed geometry of the microstructure is here used for 3D calculations of the electrochemical processes in the electrode. In addition, the area specific resistance (ASRcat) of the reconstructed porous cathode is calculated as a performance index. To this aim we have developed a model based on the finite element method (FEM), which numerical solution requires the use of high performance computing techniques (HPC) because of the detailed geometry. In this work we show the comparison of the 3D microstructure model with a well established 1D averaged model.